Asthma and Metabolic Syndrome - Where is the Link? - Ibrahim, Baharudin; Mostafa, Arwa Mohamed Amin (Faculty of Pharmacy and Science, University of Muhammadiyah Prof. DR. HAMKA, 2016)
Asthma is a major burden on global health care system which is encumbering all regions in the world. Several risk factors can induce and exacerbate asthma. Recent compelling evidences have associated metabolic syndrome with the incidence of asthma. The abdominal obesity, hypertension and insulin resistance are metabolic syndrome criteria which are substantially involved in inducing and exacerbating asthma. Several mechanisms are involved in the association between metabolic syndrome and asthma. It could be due to mechanical reason, genetic factors, inflammatory effect, hormonal effect, insulin resistance and the effect of other co-morbidities associated with obesity.